Metabolomic Profiling of Saliva in Pediatric Dental Caries: A Scoping Review - Rosely Lydia Ingkiriwang; Arlette Suzy Setiawan (SONDE (Sound of Dentistry), 2025)
Introduction : Dental caries is one of the most common chronic oral diseases in children. Its development involves complex interactions among diet, oral microbiota, host factors, and saliva. Salivary metabolomics, the analysis of small molecules in saliva, has emerged as a promising approach to identify biomarkers associated with caries. This scoping review aims to map the existing evidence on salivary metabolomics in pediatric caries, focusing on analytical methods, major findings, and clinical implications. Methods : Following PRISMA-ScR guidelines, PubMed, Scopus, and ScienceDirect were searched for English-language articles published between 2015 and 2025. Eligible studies included participants ≤18 years old, applied validated metabolomic platforms, and investigated salivary metabolites in relation to dental caries. Studies not using saliva, involving adults, systemic diseases, or non-metabolomic approaches were excluded. Results and Discussion : Eight studies fulfilled the inclusion criteria. NMR and LC-MS were the most common platforms. Frequently reported metabolites elevated in caries-active children included acetate, lactate, formate, and certain amino acids such as tyrosine and glycine. These metabolic shifts reflect bacterial activity and amino acid breakdown. However, methodological differences limited comparability across studies, and evidence from longitudinal or predictive modeling studies remains scarce. Conclusion : Salivary metabolomics offers promise for identifying non-invasive biomarkers of pediatric caries. While preliminary data are encouraging, consistent methodologies and larger studies are needed to validate metabolomic markers for early diagnosis and caries risk assessment.